POSS-cored and peptide functionalized ternary gene delivery systems with enhanced endosomal escape ability for efficient intracellular delivery of plasmid DNA. Issue 25 (20th June 2018) - Hao, Xuefang; Li, Qian; Ali, Hasnain; Zaidi, Syed Saqib Ali; Guo, Jintang; Ren, Xiangkui; Shi, Changcan; Xia, Shihai; Zhang, Wencheng; Feng, Yakai
Abstract : POSS-cored, CPP, NLS and REDV peptide functionalized ternary gene delivery systems for efficient intracellular delivery of plasmid DNA. Abstract : Biocompatibility, stability and high efficiency profiles are critical points for promoting the practical applications of gene delivery systems. The incorporation of cell-penetrating peptides (CPPs), REDV, and a nuclear localization signal (NLS) peptide sequence has been considered to be a promising strategy for developing efficient gene carriers to transfect vascular endothelial cells (ECs). However, these integrated multifunctional peptide carriers are usually limited by their inefficient targeting function and weak endosomal escape ability. Aiming to develop more efficient gene carriers, the integrated multifunctional REDV-G-TAT-G-NLS-C sequence was conjugated to polyhedral oligomeric silsesquioxane (POSS) by heterobifunctional poly(ethylene glycol) in the current study. This star-shaped polymer carrier complexed with the pZNF580 plasmid to form gene complexes, and then the histidine-rich peptide of REDV-TAT-NLS-H12 (TP-H12) was incorporated into their surface to obtain ternary gene delivery systems with enhanced endosomal escape ability. These ternary gene delivery systems exhibited low cytotoxicity towards ECs and possessed high REDV-mediated cellular uptake, excellent internalization efficiency, rapid endosomal escape and high nucleus translocation capacity. The endosomal escape of the ternary complexes was improved due to the pH buffering capacity of the histidine residue in TP-H12 and the optimized macropinocytosis internalization pathway. Moreover, these CPP-based ternary gene delivery systems have high gene delivery efficiency and could improve the migration of ECs as demonstrated by gene expression and transwell assay. These systems may serve as a promising candidate for gene delivery and transfection in ECs, which is advantageous for EC migration and endothelialization on the biomaterial surface.